# SBP-Program

## Adding and subtracting monomials with different exponents

How to add and subtract monomials with different exponents? How do you add and subtract monomials with different exponents?

### Examples of adding and subtracting monomials with different exponents

Example of adding and subtracting monomials with different exponents.

Add and subtract the following monomials with different exponents

8d6 + 6d5d - 5d6

Solution.

8d6 + 6d5d - 5d6 =
8d6 + 6d5d1 - 5d6 =
8d6 + 6d5 + 1 - 5d6 =
8d6 + 6d6 - 5d6 = 9d6

Answer: 9d6.

Example of adding and subtracting monomials with different exponents.

Add and subtract the following monomials with different exponents

26c2d + 4ccd - 5c2d

Solution.

26c2d + 4ccd - 5c2d =
26c2d + 4c1c1d - 5c2d =
26c2d + 4c1 + 1d - 5c2d =
26c2d + 4c2d - 5c2d = 25c2d

Answer: 25c2d.

Example of adding and subtracting monomials with different exponents.

Add and subtract the following monomials with different exponents

7dd + d2 - 6d2

Solution.

7dd + d2 - 6d2 =
7d1d1 + d2 - 6d2 =
7d1 + 1 + d2 - 6d2 =
7d2 + 1d2 - 6d2 =
2d2

Answer: 2d2.

Example of adding and subtracting monomials with different exponents.

Add and subtract the following monomials with different exponents

25y9 - y9 + x9

Solution.

25y9 - y9 + x9 =
25y9 - 1y9 + x9 =
24y9 + x9

Answer: 24y9 + x9.

Note, we can only add like terms (monomials) and we cannot add unlike terms (monomials).